THE INLUENCE OF COUTING BOARD MEDIA IN ADDITION AND SUBTRACT MATERIAL ON THE COMPUTATION THINGKING ABILITY OF CLASS I STUDENTS AT SDN 177 PALEMBANG - Affifa Bella Franita; Nora Sumilasari; Dian Nuzulia Armariena (SMART: Journal of Multidisciplinary Educational, 2023)
Technology has become a part of human life. Almost all aspects of human life now use technology, especially the use of computers. With the increasingly massive era of computerisation like this, humans must be able to start understanding computer algorithms even from an early age. Computing can not only be introduced to computer subjects, computational thinking is a thought process based on computer science but can be applied in other disciplines. This study aims to determine the effect of smart board counting media on addition and subtraction material on computational thinking skills of grade 1 students at SD N 177 Palembang. The method used in this research is experimental research method. This study used the Pottest-Only Control Design research type. This design conducted two classes to measure the ability of computational thinking on addition and subtraction material of students of class 1A and 1.C SD N 177 Palembang. In this research, the data collection techniques used were documentation, observation and test. The results of the study stated that the results of the hypothesis test of the posttest data of the control class and the experimental class obtained the t value of 6.130 and the t table value of 1.675 with α = 0.05 and df = 51, then t count = 6.130> t table = 1.675. In accordance with the prerequisites of hypothesis testing, it can be concluded that H0 is rejected and Ha is accepted or there is an effect of counting board media on addition and subtraction material on the computational thinking skills of grade 1 students at SD N 177 Palembang